Unveiling “Mid-Pliocene Warm Period” dynamics through multiproxy stratigraphic analysis: The Valdelsa Basin in Northern Apennines – Italy as a key archive - L. Milaneschi; G. Cornamusini; P. Conti; I. Martini; J. Maffei; F. Cifelli; M. Mattei; S. Da Prato; M.C. Alçiçek; L.M. Foresi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

Exploring light-effects of microalgal extract on zebrafish caudal fin cell regeneration for aquaculture applications - F. Conti; E. Frigato; E. Ruohisto; J. F. López-Olmeda; F. J. Sánchez-Vázquez; C. Baldisserotto; C. Bertolucci; S. Pancaldi (Aquaculture International, 2026)

The daily rhythms of temperature preference are conserved in nocturnal and blind fish - F. Conti; E. Gatto; G. de Alba; S. Pintos; J.F. López-Olmeda; L.M. Vera; S. Rey Planellas; S.A. Mackenzie; C. Bertolucci; F.J. Sánchez-Vázquez (Journal of Thermal Biology, 2025)

Natural-based solutions to mitigate dietary microplastics side effects in fish - N. Cattaneo; M. Zarantoniello; F. Conti; A. Tavano; A. Frontini; I. Sener; G. Cardinaletti; I. Olivotto (Chemosphere, 2024)

Lectotypification and taxonomy of the Italian endemic Biscutella incana (Brassicaceae) - F. Bartolucci; F. Conti (Plant Biosystems, 2024)

P13-17 Assessment of the efficiency of the literature search of the ten key characteristics of carcinogens in the IARC Monographs evaluation process - C. Facchin; A. De Conti; L. Benbrahim-Tallaa; S. Chittiboyina; S. Ruiz; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2024)

Effect of different deficit irrigation regimes on vine performance, grape composition and wine quality of the “Primitivo” variety under mediterranean conditions - P. Losciale; L. Conti; S. Seripierri; V. Alba; F. Mazzone; L. Rustioni; G. di Leo; F. Tarricone; L. Tarricone (Irrigation Science, 2024)
Climate change represents one of the current major challenges and the improper use of water resources is an impeding threat. Agricultural research can play a crucial role by developing innovative strategies and techniques to reduce water use without affecting crop productivity and quality, particularly in grapevine growing in Mediterranean areas, as both productivity and wine quality are quintessential for the economic and ecologic sustainability of this crop. The present study aimed to define a deficit irrigation strategy for the “Primitivo” grapevine cultivar, taking into account the overall pathway of the vineyard performance in terms of leaf functionality, starch reserves, vine productivity, and wine quality. The trial was carried out in Southern-Italy on a three year-old, drip irrigated vineyard, imposing four deficit irrigation regimes for two consecutive seasons, consisting of 29 (T29), 55 (T55), 85 (T85) and 100% (T100) of crop evapotranspiration (ET C ). Mild water restriction (T85) did not affect vegetative nor reproductive vine performance. Deficit irrigation at 55% ET C lowered leaf functionality, starch accumulation, vine vigour and yield, due to a reduction of cluster weight; however, wine acidity and phenolic compounds were increased. T29 further decreased yield, as also the number of clusters was reduced. The most water-stressed treatment revealed a low concentration of malic acid in the must and a consequent increase of the ethanol sensation in the wine. After 9 months ageing, T85 had the highest wine colour intensity suggesting this treatment as the most promising in terms of quality and quantity of wine as well as for water saving.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Breast density in NF1 women: a retrospective study - R. De Santis; G. Cagnoli; B. Rinaldi; D. Consonni; Beatrice Conti; M. Eoli; A. Liguori; M. Cosentino; G. Carrafiello; O. Garrone; M. Giroda; C. Cesaretti; et al. (Familial Cancer, 2024)
Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by neurofibromin haploinsufficiency due to pathogenic variants in the NF1 gene. Tumor predisposition has long been associated with NF1, and an increased breast cancer (BC) incidence and reduced survival have been reported in recent years for women with NF1. As breast density is another known independent risk factor for BC, this study aims to evaluate the variability of breast density in patients with NF1 compared to the general population. Mammograms from 98 NF1 women affected by NF1, and enrolled onto our monocentric BC screening program, were compared with those from 300 healthy subjects to verify differences in breast density. Mammograms were independently reviewed and scored by a radiologist and using a Computer-Aided Detection (CAD) software. The comparison of breast density between NF1 patients and controls was performed through Chi-squared test and with multivariable ordinal logistic models adjusted for age, body mass index (BMI), number of pregnancies, and menopausal status.breast density was influenced by BMI and menopausal status in both NF1 patients and healthy subjects. No difference in breast density was observed between NF1 patients and the healthy female population, even after considering the potential confounding factors.Although NF1 and a highly fibroglandular breast are known risk factors of BC, in this study, NF1 patients were shown to have comparable breast density to healthy subjects. The presence of pathogenic variants in the NF1 gene does not influence the breast density value.

New olive-pomace fertilizer tested with a 2-tiers approach: Biomarkers on Eisenia fetida, physiochemical effects on Solanum lycopersicum and Olea europaea - S. Parri; T. Campani; V. Conti; G. Cai; M. Romi; S. Casini; R. Zari; F. Caldini; L. Marsili (Journal of Environmental Management, 2024)

P03-14: Cancer Hazard Identification in the IARC Monographs: Recent evaluations for which cancer in experimental animals and toxicological evidence was influential - L. Benbrahim-Tallaa; F. El Ghissassi; A. De Conti; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2023)

OS02-04: Advancing the evaluation of mechanistic evidence in cancer hazard identification: update on the IARC key characteristic (KCs) of carcinogens framework - F. Madia; A. De Conti; F. El Ghissassi; L. Benbrahim-Tallaa; M. Schubauer-Berigan (Toxicology Letters, 2023)

Tumor and peritumoral adipose tissue crosstalk: De-differentiated adipocytes influence spread of colon carcinoma cells - G. Conti; L. Calderan; L.A. Quintero Sierra; A. Conti; R. Ossanna; F. Boschi; P. Marzola; F. Ferrarini; M. Governa; P.M.-J. Lievens; A. Sbarbati (Tissue and Cell, 2023)

Juvenile polyposis diagnosed with an integrated histological, immunohistochemical and molecular approach identifying new SMAD4 pathogenic variants - Andrea Mafficini; Lodewijk A. A. Brosens; Maria L. Piredda; Cristian Conti; Paola Mattiolo; Giulia Turri; Maria G. Mastrosimini; Sara Cingarlini; Stefano F. Crinò; Matteo Fassan; Paola Piccoli; Michele Simbolo; et al. (Familial Cancer, 2022)
Juvenile polyposis (JP) is a rare familial syndrome characterized by the development of numerous hamartomatous polyps of the gastrointestinal tract and by an increased risk of developing gastrointestinal cancers. It follows a pattern of autosomal dominant inheritance and is associated with germline variants of SMAD4 or BMPR1A genes. Differential diagnosis may be difficult based on histology alone, due to morphological similarities to other familial syndromes. Here we report a case of familial JP diagnosed in a 50-years woman with a familial history positive for gastrointestinal cancers and other tumor types. The patient presented with severe iron deficiency anemia and showed numerous polyps in the stomach and jejunum according to endoscopy and imaging. She underwent an intra-gastric laparoscopic removal of the major gastric polyp, followed by jejunal exploration and resection of a segment with multiple neoformations. Histological examination revealed the presence of hamartomatous polyposis. Gastric and intestinal samples were analyzed with next-generation sequencing. Molecular analysis showed that the patient harbored a germline splicing site variant of SMAD4 , c.1139 + 3A > G, which was complemented by different somatic variants of the same gene in the different polyps. Immunohistochemistry for SMAD4 confirmed loss of protein expression in the polyps, with regular expression in normal cells. cDNA sequencing further confirmed the findings. We thus definitively diagnosed the woman as having JP thanks to an integrated approach based on histology, immunohistochemistry and molecular analysis. The identified variants, all previously reported as variants of unknown significance, were classified as pathogenic as they complemented each other leading to SMAD4 loss.

Unraveling the Lagged Effect of Hydro-meteorological Conditions On the Trophic State of a Reservoir By Applying Dynamic Regression - Pablo F. Andreoni; Marcia A. Ruiz; María Inés Rodríguez; Ana Laura Ruibal-Conti (Water Resources Management, 2022)

Barcoding helps threatened species: the case of Iris marsica (Iridaceae) from the protected areas of the Abruzzo (Central Italy) - O. De Castro; E. Del Guacchio; E. Di Iorio; A. Di Maio; L. Di Martino; F. Bartolucci; F. Conti (Plant Biosystems, 2020)

Correction to: Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Circulating miRNAs expression as potential biomarkers of mild traumatic brain injury - Francesca Polito; Fausto Famà; Rosaria Oteri; Giovanni Raffa; Gianluca Vita; Alfredo Conti; Sacco Daniele; Vincenzo Macaione; Marcello Passalacqua; Salvatore Cardali; Rosa Maria Di Giorgio; Maria Gioffrè; et al. (Molecular Biology Reports, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Microparticles and autophagy: a new frontier in the understanding of atherosclerosis in rheumatoid arthritis - C. Barbati; M. Vomero; T. Colasanti; F. Ceccarelli; M. Marcosano; F. Miranda; L. Novelli; A. Pecani; Carlo Perricone; F. R. Spinelli; S. Truglia; F. Conti; et al. (Immunologic Research, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

Altered soil carbon dynamics under different land-use regimes in subtropical seasonally-dry forests of central Argentina - G. Conti; E. Kowaljow; F. Baptist; C. Rumpel; A. Cuchietti; N. Pérez Harguindeguy; S. Díaz (Plant and Soil, 2016)

Fatigue of Metallic Stents: From Clinical Evidence to Computational Analysis - F. Auricchio; A. Constantinescu; M. Conti; G. Scalet (Annals of Biomedical Engineering, 2016)

Optical Characterization of Normal, Benign, and Malignant Thyroid Tissue: A Pilot Study - M. P. Brandao; R. Iwakura; F. S. Basilio; K. Haleplian; A. S. Ito; L. C. Conti de Freitas; L. Bachmann (Journal of Fluorescence, 2015)

Erratum to: Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Topo‐climatic microrefugia explain the persistence of a rare endemic plant in the Alps during the last 21 millennia - Theofania S. Patsiou; Elena Conti; Niklaus E. Zimmermann; Spyros Theodoridis; Christophe F. Randin (Global Change Biology, 2014)
Ongoing rapid climate change is predicted to cause local extinction of plant species in mountain regions. However, some plant species could have persisted during Quaternary climate oscillations without shifting their range, despite the limited evidence from fossils. Here, we tested two candidate mechanisms of persistence by comparing the macrorefugia and microrefugia ( MR ) hypotheses. We used the rare and endemic Saxifraga florulenta as a model taxon and combined ensembles of species distribution models ( SDM s) with a high‐resolution paleoclimatic and topographic dataset to reconstruct its potential current and past distribution since the last glacial maximum. To test the macrorefugia hypothesis, we verified whether the species could have persisted in or shifted to geographic areas defined by its realized niche. We then identified potential MR based on climatic and topographic properties of the landscape and applied refined scenarios of MR dynamics and functions over time. Last, we quantified the number of known occurrences that could be explained by either the macrorefugia or MR model. A consensus of two or three SDM techniques predicted absence between 14–10, 3–4 and 1 ka bp , which did not support the macrorefugia model. In contrast, we showed that S. florulenta could have contracted into MR during periods of absence predicted by the SDM s and later re‐colonized suitable areas according to the macrorefugia model. Assuming a limited and realistic seed dispersal distance for our species, we explained a large number of the current occurrences (61–96%). Additionally, we showed that MR could have facilitated range expansions or shifts of S. florulenta . Finally, we found that the most recent and the most stable MR were the ones closest to current occurrences. Hence, we propose a novel paradigm to explain plant persistence by highlighting the importance of supporting functions of MR when forecasting the fate of plant species under climate change.

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Taxonomic notes on Geum micropetalum Gasp. and Geum heterocarpum Boiss. (Rosaceae) in Italy - F. Bartolucci; F. Conti (Plant Biosystems, 2013)

Fine resolution distribution modelling of endemics in Majella National Park, Central Italy - H. van Gils; F. Conti; G. Ciaschetti; E. Westinga (Plant Biosystems, 2012)

Mapping of main and epistatic effect QTLs associated to grain protein and gluten strength using a RIL population of durum wheat - Veronica Conti; Pablo F. Roncallo; Valeria Beaufort; Gerardo L. Cervigni; Ruben Miranda; Carlos A. Jensen; Viviana C. Echenique (Journal of Applied Genetics, 2011)

Haplotypes of the bovine IgG2 heavy gamma chain in tick-resistant and tick-susceptible breeds of cattle - Wanessa Araújo Carvalho; Patricia Ianella; Frederico G. C. Arnoldi; Alexandre Rodrigues Caetano; Sandra Regina Maruyama; Beatriz Rossetti Ferreira; Luís Henrique Andreucci Conti; Marcia Ramos Monteiro da Silva; José Otavio F. Paula; Antonio Augusto Mendes Maia; Isabel K. Ferreira de Miranda Santos (Immunogenetics, 2011)

A new species of Lathyrus L. (Fabaceae) from Central Apennine (Italy) - F. Conti (Plant Biosystems, 2010)

A case of primary papillary disseminated adenocarcinoma of canine lung - Maria Beatrice Conti; M. C. Marchesi; G. Angeli; E. Lepri; C. Marinetti; F. Rueca (Veterinary Research Communications, 2010)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Olive oil adulterated with hazelnut oils: simulation to identify possible risks to allergic consumers - M. Arlorio; J.D. Coisson; M. Bordiga; F. Travaglia; C. Garino; L. Zuidmeer; R. Van Ree; M.G. Giuffrida; A. Conti; A. Martelli (Food Additives & Contaminants: Part A, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

Clinical findings and diagnosis in a case of cholangiocellular carcinoma in a horse - M. B. Conti; M. C. Marchesi; F. Zappulla; D. Buttarelli; E. Lepri; F. Passamonti; S. Galletti; G. Rucco; F. Rueca (Veterinary Research Communications, 2008)

γ-Irradiation of PEGd,lPLA and PEG-PLGA Multiblock Copolymers: I. Effect of Irradiation Doses - R. Dorati; C. Colonna; M. Serra; I. Genta; T. Modena; F. Pavanetto; P. Perugini; B. Conti (AAPS PharmSciTech, 2008)

Thrusting and faulting in metamorphic and sedimentary units of Ligurian Alps: an example of integrated field work and geochemical analyses - F. Piana; S. Tallone; S. Cavagna; A. Conti (International Journal of Earth Sciences, 2006)

5-Methyl-Pyrrolidinone Chitosan Films as Carriers for Buccal Administration of Proteins - C Colonna; I Genta; P Perugini; F Pavanetto; T Modena; M Valli; C Muzzarelli; B Conti (AAPS PharmSciTech, 2006)

Diet and cooling interactions on physiological responses of grazing dairy cows, milk production and composition - M. R. Gallardo; S. E. Valtorta; P. E. Leva; M. C. Gaggiotti; G. A. Conti; R. F. Gregoret (International Journal of Biometeorology, 2005)

Blood Pressure Measurements in Dogs and Horses Using the Oscillometric Technique: Personal Observations - F. Porciello; F. Birettoni; M.B. Conti; C. Marinetti; M.T. Antognoni; G. Fruganti (Veterinary Research Communications, 2004)

Asyneuma pichleri (Campanulaceae), a neglected species of the Balkan Peninsula - D. Lakušić; F. Conti (Plant Systematics and Evolution, 2004)

Diagnosis and Treatment of Progressive Ethmoidal Haematoma (PEH) in Horses - M.B. Conti; M.C. Marchesi; F. Rueca; M. Puccetti (Veterinary Research Communications, 2003)

Chronic Renal Failure (CRF) in Horses: Personal Reports - F. Rueca; F. Porciello; M.B. Conti; M.C. Marchesi (Veterinary Research Communications, 2003)

Geochemical changes at the Bagni di Triponzo thermal spring during the Umbria-Marche 1997–1998 seismic sequence - F. Quattrocchi; R. Pik; L. Pizzino; M. Guerra; P. Scarlato; M. Angelone; M. Barbieri; A. Conti; B. Marty; E. Sacchi; G.M. Zuppi; S. Lombardi (Journal of Seismology, 2000)

Expression of lymphocyte subpopulations, cytokine serum levels, and blood and urinary trace elements in asymptomatic atopic men exposed to an urban environment - P. Boscolo; M. Di Gioacchino; E. Sabbioni; F. Benvenuti; P. Conti; M. Reale; P. Bavazzano; G. Giuliano (International Archives of Occupational and Environmental Health, 1999)

Calcium dependent shifts of Na + channel activation correlated with the state dependence of calcium-binding to the pore - A. Boccaccio; O. Moran; F. Conti (European Biophysics Journal, 1998)

Deoxyribonucleic acid base compositions of hyphomicrobia - M. Mandel; P. Hirsch; S. F. Conti (Archives of Microbiology, 1972)

Electron microscope studies on Leucothrix mucor - Thomas D. Brock; S. F. Conti (Archives of Microbiology, 1969)

Biology of budding bacteria - Peter Hirsch; S. F. Conti (Archives of Microbiology, 1964)

Biology of budding bacteria - Peter Hirsch; S. F. Conti (Archives of Microbiology, 1964)